Molecular Characteristics of Community-Associated Staphylococcus aureus Isolates From Pediatric Patients With Bloodstream Infections Between 2012 and 2017 in Shanghai, China - Wang, Xing; Liu, Qian; Zhang, He; Li, Xia; Huang, Weichun; Fu, Qihua; Li, Min (Frontiers in Microbiology, 2018)
Staphylococcus aureus is known as an invasive human pathogen, resulting in significant morbidity and mortality worldwide; however, information on community-associated S. aureus (CA-SA) from bloodstream infections (BSI) in children in China remains scarce. This study aimed to investigate the molecular characteristics of 78 CA-SA isolates recovered from pediatric patients with BSI between 2012 and 2017 in Shanghai. All isolates including 51 (65.4%) methicillin-susceptible S. aureus (MSSA) and 27 (34.6%) methicillin-resistant S. aureus (MRSA) isolates were characterized based on antimicrobial resistance, virulence genes, multilocus sequence typing (MLST), spa, and SCCmec typing. A total of 18 distinct sequence types (STs) and 44 spa types were identified. ST188 and ST7 were the predominant MSSA clones and ST59-MRSA-SCCmecIV/V was the most common MRSA clone. Spa t189 (9.0%, 7/78) was the most common spa type. SCCmec types IV and V were observed at frequencies of 59.3% and 40.7%, respectively. Notably, 40 (51.3%) S. aureus BSI strains were multidrug resistant (MDR), and these were mostly resistant to penicillin, erythromycin, and clindamycin. MRSA strains were associated with substantially higher rates of resistance to multiple antibiotics than MSSA strains. Fifty (64.1%, 50/78) isolates, including 19 (70.3%) MRSA isolates, harbored ≥ 10 tested virulence genes, as evaluated in this study. Ten (37.0%) MRSA isolates and four (7.8%) MSSA isolates harbored the gene encoding Panton–Valentine leukocidin (PVL). Virulence genes analysis showed diversity in different clones; the seb-sek-seq genes were present in all ST59 strains, whereas the seg-sei-sem-sen-seo genes were present in different clones including ST5, ST20, ST22, ST25, ST26, ST30, ST121, and ST487 strains. In conclusion, this study revealed that community-associated S. aureus strains from BSI in children demonstrated considerable genetic diversity, and identified major genotypes of CA-MRSA and CA-MSSA, with a high prevalence of CA-MRSA. Furthermore, major genotypes were frequently associated with specific antimicrobial resistance and toxin gene profiles. Understanding the molecular characteristics of those strains might provide further insights regarding the spread of BSI S. aureus among children between communities in China.